Soil-health management in nutrient-deficient soils: A case study of Indian farmers - KUMAR, PAWAN; SHEHRAWAT, P S; KUMAR, RAJ; ASHMA, ASHMA; SHUBHAM, SHUBHAM; KHAN, MUJAHID (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out in two agro-climatic zones of the state of Haryana in India, viz. north-easternzone and south-western zone with the objective that how farmers approach soil-health management in nutrientdeficient soils. The outcomes have been visualised in this paper after conducting a field survey during 2018–19 of 240 farmers, who were interviewed with a well-structured interview schedule. The study found that respondents’ awareness level was good about the Integrated Nutrient Management (INM), had a rich knowledge about Integrated Farming System (IFS) and were well aware about organic farming. Major constraints faced by the respondents in INM, IFS and organic farming were ‘high fertilizer cost and manures are bulky to handle’, ‘high rate of interest on borrowings and initial cost of production’ and ‘prices are not remunerative’, respectively. The study concluded that there was a gap in awareness level of soil health management practices among the farmers. Hence, there is an immense need to motivate and encourage the farmers.